Tolerance : The Beacon of the Enlightenment - Caroline Warman
Inspired by Voltaire's advice that a text needs to be concise to have real influence, this anthology contains fiery extracts by forty eighteenth-century authors, from the most famous philosophers of the age to those whose brilliant writings are less well-known. These passages are immensely diverse in style and topic, but all have in common a passionate commitment to equality, freedom, and tolerance. Each text resonates powerfully with the issues our world faces today. Tolerance was first published by the Société française d'étude du dix-huitième siècle (the French Society for Eighteenth-Century Studies) in the wake of the Charlie Hebdo assassinations in January 2015 as an act of solidarity and as a response to the surge of interest in Enlightenment values. With the support of the British Society for Eighteenth-Century Studies, it has now been translated by over 100 students and tutors of French at Oxford University.